Form Follows Function? Re-questioning the Dilemma of Form Vs Function in Contemporary Egyptian Architecture - Kesseiba, Karim (European Journal of Multidisciplinary Studies, 2019)
Based on the debate continuously raised by architects and theorists regarding the dilemma of “form Vs function”, it is important to reflect on the issue in regards of contemporary architecture. Stemming from Le Corbusier’s manifesto, “The house is a machine to live in”, many interpretations have been made, with one group arguing the importance of demolishing all aspects other than functionality when dealing with an architectural addition to the built environment. The other group adopt the philosophy that “International Architecture” was tailored for a specific time, which has to be dir-regarded now in order to fulfill contemporary architectural needs. The debate which the paper will discuss is based on understanding the origins from which the competition between form and functions stemmed. The paper also questions whether form is currently a function in the era of Globalization in the shadows of branding and starchitects signature designs. This debate will be reflected on major iconic buildings in Egypt; The Grand Egyptian Museum, Museum of Egyptian Civilization and Alexandria Bibliotheca. Those three cases were specifically selected since they were major state-led competitions which influenced the trends of architecture in Egypt for decades. The methodology of the paper is based on primarily explaining the origins of the manifestos by pioneer architects calling for the victory of function over form. Following that, a discussion based on critical observations from contemporary architecture will be presented to show how form is currently considered a function, especially when politicians aim to produce iconic architecture. Finally, the three case studies will be analyzed according to the relevance of form to function and how the iconic effect produced influences after completion. The case study will demonstrate that form and function are the two sides of one coin, and instead of urging to prove one is prior to the other, it is more important fulfill what the goals of the architectural product.
Keywords: Contemporary architecture; form follows function; Egyptian Architecture.